Selenium and Zinc Oxide Multinutrient Supplementation Enhanced Growth Performance in Zebra Fish by Modulating Oxidative Stress and Growth-Related Gene Expression - Fasil, Dawit Moges; Hamdi, Hamida; Al-Barty, Amal; Zaid, Abeer Abu; Parashar, S. K. S.; Das, Biswadeep (Frontiers in Bioengineering and Biotechnology, 2021)
Selenium and zinc are important dietary micronutrients having antimicrobial and antioxidant roles, thereby assisting in normal development and enhanced immune system. Supplementation of selenium and zinc for enhancing the growth performance and reproductive capacity in fish was explored in this study. Selenium (SeNPs) and zinc oxide nanoparticles (ZnONPs) were synthesized by high-energy ball milling (HEBM) using a 10-hour dry milling technique at 10:1 ball-to-powder ratio (BPR) and were premixed with basal feed followed by the administration to adult zebrafish (Danio rerio) (2 months old) for 30 days. Growth analysis revealed that zebrafish fed with SeNPs + ZnONPs (2 mg/kg, equimolar mixture) had significantly higher length and weight compared to only SeNPs (2 mg/kg) or ZnONPs (2 mg/kg) groups and control zebrafish (p < 0.05). The average length-weight relationships were assessed by estimating the condition factor (C), which was highest in the SeNPs + ZnONPs group (1.96), followed by a downward trend in SeNP (K= 1.15) and ZnONP (1.11) (p < 0.05). Relative gene expression of growth hormone and insulin-like growth factor-1 were significantly high in the SeNPs + ZnONPs compared to other groups (p < 0.05), which indicated that combined administration of both the nanoparticles in basal feed enhanced the growth performance of zebrafish. Intracellular ROS generation was low in the combined group, followed by control, SeNPs, and ZnONPs groups, indicating higher concentrations of both nanoparticles, in particular, ZnONPs induced oxidative stress. Fecundity and the development of fertilized embryos were significantly high in the SeNPs + ZnO-NPs-treated zebrafish compared to only SeNP or ZnO-NP-treated or control (p < 0.05). These findings indicated that supplementation of SeNP + ZnONP in basal feed could considerably improve the growth performance and development of zebrafish that could be exploited for enhancing aquaculture production.